Biscuit Loves Father's Day - Capucilli, Alyssa Satin 1957- (New York : HarperFestival, 2004)
A dog follows the bus to school, where he meets the teacher and takes part in the activities of the class.
Keywords: Dogs -- Fiction; Fiction